VISCERAL LEISHMANIASIS IN ADULTS - Idris, Muhammad; Farid, Jamila; Gul, Nasreen; Ahmed, Fiaz; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2017)
Visceral Leishmaniasis (also known as Kala Azar) is a parasitic infection caused by Leishmania Donovani in the East and Leishmania Infantum in the west. It is prevalent in many countries including India, Bangladesh, Nepal, Africa and part of America. The disease follows chronic course and is usually lethal if left untreated. It has also been reported from different parts of Pakistan, including Northern areas, Districts Mansehra & Abbottabad and Hilly areas of Khyber Pukhtoonkhawah. Most the cases have been reported in paediatric population. Except one case, reported previously from Abbottabad. The present two cases were also seen in adults Keywords: Visceral Leishmaniasis; Sandfly; Kala Azar